KAJIAN INDIKATOR KEPERCAYAAN KONSUMEN AKAN ONLINE REVIEW PADA PROSES KEPUTUSAN BOOKING HOTEL SECARA ONLINE - MONICA PURNAMASARI HALIM (STIE Indonesia Malang, 2015)
This study was conducted to determine the factors that most influence consumer 's decision in booking hotels online. From the results, there are seven factors that encourage people to make booking hotels online that are the technology factor , the ease , speed , information , prices and reward. The factors which can affect consumer trust for booking hotels online. Online review is a media which can make consumer easier to choose the best website for booking hotels online.Key Words : Online Reservation, Hotel, Online Review, Consumer Trust